Uniparental disomy and pretreatment IGF-1 may predict elevated IGF-1 levels in Prader-Willi patients on GH treatment. (October 2019) - Palmieri, Viviana Valeria; Lonero, Antonella; Bocchini, Sarah; Cassano, Gilda; Convertino, Alessio; Corica, Domenico; Crinò, Antonio; Fattorusso, Valentina; Ferraris, Silvio; Fintini, Danilo; Franzese, Adriana; Grugni, Graziano; et al.
Abstract: Pediatric patients with Prader-Willi syndrome (PWS) can be treated with recombinant human GH (rhGH). These patients are highly sensitive to rhGH and the standard doses suggested by the international guidelines often result in IGF-1 above the normal range. We aimed to evaluate 1 the proper rhGH dose to optimize auxological outcomes and to avoid potential overtreatment, and 2 which patients are more sensitive to rhGH. In this multicenter real-life study, we recruited 215 patients with PWS older than 1 year, on rhGH at least for 6 months, from Italian Centers for PWS care. We collected auxological parameters, rhGH dose, IGF-1 at recruitment and (when available) at start of treatment. The rhGH dose was 4.3 (0.7/8.4) mg/m 2 /week. At recruitment, IGF-1 was normal in 72.1% and elevated in 27.9% of the patients. In the group of 115 patients with IGF-1 available at start of rhGH, normal pretreatment IGF-1 and uniparental disomy were associated with elevated IGF-1 during the therapy. No difference in height and growth velocity was found between patients treated with the highest and the lowest range dose. The rhGH dose prescribed in Italy seems lower than the recommended one. Normal pretreatment IGF-1 and uniparental disomy are risk factors for elevated IGF-1. The latter seems to be associated with higher sensitivity to GH. In case of these risk factors, we recommend a more accurate titration of the dose to avoid overtreatment and its potential side effects. Highlights: Height, growth velocity and BMI of the lowest rhGH dose quartile are similar to those of the highest one In our study, PWS patients are on 4.3 mg/m 2 /week of rhGH and IGF-1 is above the normal range in about 28% of the patients Low pretreatment IGF-1 and deletion of the paternal 15q11.2–q13 region predict normal IGF-1 during the rhGH treatment Patients with PWS due to uniparental disomy seem to feature a higher sensitivity to rhGH than patients with deletion